Parametric compression of information of airborne recorders in the process of copying it - Малежик, А. И.; Остапенко, A. C.; Цветков, М. М. (Proceedings of National Aviation University (archive), 2000)
Considered is the problem of decreasing the required computer memory capacity for storing the flight recorder data, i.e. parametric compression of information. Formulated are the main conception and compressibility indexes. Also considered are general principles of computer compression. Illustrated is the dynamics of changes of compressibility indexes in the process of copying parametric information under real conditions. The results of the research can be used for analysis and synthesis of computer algorithms of parametric compression of information